2020
DOI: 10.1080/23744235.2020.1784457
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of National Early Warning Score 2 (NEWS2) for intensive care unit admission in patients with SARS-CoV-2 infection

Abstract: Background: From January 2020, Coronavirus disease 19 (COVID-19) has rapidly spread all over the world. An early assessment of illness severity is important for the stratification of patients. We analysed the predictive value of National Early Warning Score 2 (NEWS2) for intensive care unit admission (ICU) in patients with Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 16 publications
5
87
0
5
Order By: Relevance
“…Gidari et al showed that the predictive value of admission NEWS2 values for ICU admission in 68 patients with severe COVID-19 was good (AUROC = 0.90 (CI, 0.82–0.97)). 33 Peng et al showed similar AUROC values for predicting ‘serious events’ of 0.837 (0.748−0.943) for admission NEWS and 0.846 (0.735−0.939) for admission NEWS modified by age, where ‘serious events’ were defined as any of the following during hospitalisation: death, unplanned transfer to an ICU or initiation of non-invasive ventilation. 34 Covino et al reported that NEWS was the most accurate predictor of ICU admission within 48 h (AUROC = 0.802 (0.756−0.844)) and 7 days (AUROC 0.783 (0.735−0.826)) of emergency department arrival.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Gidari et al showed that the predictive value of admission NEWS2 values for ICU admission in 68 patients with severe COVID-19 was good (AUROC = 0.90 (CI, 0.82–0.97)). 33 Peng et al showed similar AUROC values for predicting ‘serious events’ of 0.837 (0.748−0.943) for admission NEWS and 0.846 (0.735−0.939) for admission NEWS modified by age, where ‘serious events’ were defined as any of the following during hospitalisation: death, unplanned transfer to an ICU or initiation of non-invasive ventilation. 34 Covino et al reported that NEWS was the most accurate predictor of ICU admission within 48 h (AUROC = 0.802 (0.756−0.844)) and 7 days (AUROC 0.783 (0.735−0.826)) of emergency department arrival.…”
Section: Discussionmentioning
confidence: 96%
“…Our study provides data from a large cohort of unselected hospital admissions and focuses on an outcome measure that is both clinically relevant and has the potential to be averted with the appropriate and timely clinical intervention. Unlike other journal publications, 33 , 34 , 35 , 36 , 37 it uses NEWS and NEWS2 values from the whole hospital admission and compares the performance of the scores in patients who had a positive RT-PCR test result for SARS-CoV-2 with several other patient groups in the same hospital that were, as far as can be determined, not suffering from a COVID-19 illness. This has permitted an assessment of the need for any amendment to NEWS or NEWS2, such as the addition of age 34 , 38 or other covariates or a change in the weighting of existing parameters, 39 when evaluating patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, NEWS2 has been described as a robust tool to predict outcome during sepsis 2 and seems to predict evolution of COVID-19 upon admission to the hospital in other recently studies. [3][4][5] Considering the evolution of the epidemic, there is a need for reliable tools to predict some evolution in particular with regard to hospitalized patients, in order to discharge more quickly the patients from medical wards to home.…”
Section: Letter To the Editormentioning
confidence: 99%
“…A higher NEWS2 correlates with a higher chance of deterioration. Gidari et al 6 evaluated NEWS2 at hospital admission of patients with COVID-19 as a predictor of intensive care unit (ICU) admission. Furthermore, Kostakis et al 7 investigated association of the last or ultimate recorded NEWS2/NEWS within 24 hours of death or ICU admission in COVID-19 and non-COVID cohorts.…”
Section: Introductionmentioning
confidence: 99%